Epitope Target Structures of Fc-mediated Effector Function During HIV-1 Acquisition - Lewis, George K (2014)
PURPOSE OF REVIEW: This review analyzes recent studies suggesting that highly conserved epitopes in the HIV-1 Env trimer are targets of potentially protective non-neutralizing antibodies that mediate antibody-dependent cellular cytotoxicity (ADCC). RECENT FINDINGS: Recent studies in both non-human primates and humans, suggest that non-neutralizing antibodies play a role in blocking infection with SHIV/SIV or HIV-1 by Fc-mediated effector function, in particular ADCC. Further, several studies implicate highly conserved epitopes in the C1 region of gp120 as targets of these antibodies. However, these suggestions are controversial, as passive immunization studies do not indicate that such antibodies can block acquisition in non-human primates. Potential reasons for this discrepancy are discussed in the structural context of potent ADCC epitopes on target cells during the narrow window of opportunity when antibodies can block HIV-1 acquisition. SUMMARY: Cumulative evidence suggests that in addition to virus neutralization, Fc-mediated effector responses to highly conserved epitopes in the HIV-1 trimer play distinct as well as overlapping roles in blocking HIV-1 acquisition. Evidence will be discussed whether non-neutralizing antibodies specific for epitopes on the HIV-1 Env trimer that become exposed during viral entry contribute significantly to blocking HIV-1 acquisition.